PROFILE OF ANTIBIOTIC USE AND GERMS MAP ON PNEUMONIA PATIENTS IN THE PULMONARY ROOM Dr. ISKAK HOSPITAL, TULUNGAGUNG - Tsamrotul Ilmi; Rika Yulia; Fauna Herawati (Perpustakaan Universitas Surabaya, 2018)
Pneumonia is an infection of lung tissue caused by bacteria, fungi, viruses or parasites. Antibiotics is a major therapy in pneumonia. The aim of this study was to determine the amount of antibiotic use in DDD / lOO patient-days and to know the profile of germs map in pneumonia patients in Pulmonary Room Dr. Iskak Hospital, Tulungagung period January-June 2Ol7. Observational research method with retrospective data retrieval from patient medical record data and antibiotic usage data from Pharmacy Installation and microbiology culture result data of patient, then analyzed descriptively. The results showed the total amount of antibiotic in l3O unspecified pneumonia patients non ICU inpatient in Pulmonary Room Dr. Iskak Hospital, Tulungagung period January-June 2Ol7 was 5l.28 DDD/lOO patient-days. The most antibiotic types are levofloxacin iv 4O,l4 DDD /lOO patient-days and ceftriaxone 8.7l DDD /lOO patient- days. The profile of the pneumonia-causing germs map can not be determined because there is no data on microbiological culture test results from the patient.